Regime Nonstationarity and Nonlinearity in the Turkish Output Level - Kandemir Kocaaslan, Ozge (International Journal of Economics and Financial Issues, 2016)
In this paper, we investigate the nonlinearity and nonstationarity of Turkish output series applying a Markov regime switching augmented Dickey Fuller unit root test. We document that the output series are characterized by a two-regime Markov switching unit root process. We show that output series is stationary in one regime and nonstationary in the other one. Moreover, we observe that the nonstationary regime corresponds to the recessionary periods in the Turkish economy. That is, the shocks to output are highly persistent in the recession regime, but they are transitory in the expansion regime. In addition, the time period in which the output series is found as stationary is longer than the one in which the output series has a unit root. Keywords: Unit root, Markov regime switching model, Output. JEL Classifications: C22, C24, E23.